Geology of Piemonte region (NW Italy, Alps–Apennines interference zone). Issue 2 (30th November 2017) - Piana, F.; Fioraso, G.; Irace, A.; Mosca, P.; d'Atri, A.; Barale, L.; Falletti, P.; Monegato, G.; Morelli, M.; Tallone, S.; Vigna, G. B.
ABSTRACT: The geological map of Piemonte Region (Italy) is a graphic representation of the geology of the region, grounded on a large geodatabase, that can be also browsed as an interactive scalable map (GeoPiemonte Map) using a WebGIS application. The Map, produced at 1:250, 000 scale, is the first original release of the 'GeoPiemonte Map' project. The geological data represented on the map derive from a thorough revision of available geological maps and literature, integrated with unpublished original data. The revision and harmonisation of existing and new data have been based on explicit criteria used for the classification of geologic units and their representation on the Map. These criteria firstly aimed at providing a lithostratigraphic, hierarchic subdivision of Piemonte geologic units and describing them using shared concepts and vocabularies, consistent with IUGS Descriptive Standards for the Geosciences.